Association between perfluoroalkyl substances concentration and bone mineral density in the US adolescents aged 12-19 years in NHANES 2005-2010 - Xiong, Xianmei; Chen, Baihang; Wang, Zhongqing; Ma, Liqiong; Li, Shijie; Gao, Yijia (Frontiers in Endocrinology, 2022)
Background: Reports on the association of perfluoroalkyl substances (PFASs) exposure with adolescent bone health are scarce, and studies have primarily targeted maternal serum. Objective: We evaluated the relationship between autologous serum perfluorooctanoic acid (PFOA), perfluorosulfonic acid (PFOS), and perfluorononanoic acid (PFNA) levels and bone mineral density (BMD)in adolescents. Methods: We analyzed data from 1228 adolescents aged 12-19 years in the National Health and Nutrition Examination Survey 2005-2010 and used multiple regression analysis to identify the relationship between serum PFOA, PFOS, and PFNA concentrations and total femoral, femoral neck, and lumbar spine BMD, in addition to multiple stratified subgroup analyses. Methods: The mean age of participants was 15 years, and males had higher serum PFAS concentrations than females. The result of multiple regression analysis demonstrated a negative correlation between natural log (ln)-transformed PFOA exposure and femoral neck and lumbar spine BMD (all p < 0.05), but not total femur BMD (= -0.014, 95 CI: -0.028, 0.000), ln-PFOS and ln-PFNA were negatively associated with the total femur, femoral neck, and lumbar spine BMD (all p < 0.05). In the subgroup analysis, ln-PFOA was highly correlated with lumbar spine BMD in younger (12-15 years), ln-PFOS and lumbar spine BMD were more significant in normal weight and environmental tobacco smoke (ETS) adolescents (all p for interaction < 0.05), and ln-PFNA was more significantly associated with the total femur, femoral neck, and lumbar spine BMD in both ETS populations (all p for interaction < 0.05). Conclusions: Serum PFAS levels are associated with lower bone mineral density in a representative sample of US adolescents aged 12-19 years, particularly in younger, normal weight and ETS populations, and the association varies depending on the PFAS type and bone site examined.